A influência do Banco Interamericano de Desenvolvimento na formulação de políticas públicas: análise das condições de financiamento do programa de reabilitação da área central do município de São Paulo - Procentro - Viana, Lúcio Hanai Valeriano (2009)
This study analyses the performance of the Inter American Development Bank (IADB) in regards to public policies financing, more specifically the Programme of Revitalisation of Downtown Sao Paulo (Procentro). The observed period involves the administration of Mayor Marta Suplicy (2000 – 2004) – period when the contract signature took place – and the administration of Mayors Jose Serra/Gilberto Kassab (2004 – 2008). It aims at evaluating the influence exerted by the IADB in a specific public policy, having the Procentro case study as basis. For that, in-depth interviews with some technicians responsible for different areas of the programme and analysis of documents (contracts, programmes and reports) were made aiming at identifying the type of language used by the Bank, as well as the sort of demands and counterparts to the actual implementation of the public policy in question. These observations focused on the pre-approval and signature phases, therefore the phases understood as preconditions and conditions, respectively. Based on information gathered through the methods mentioned above, the Procentro case study allows for the conclusion that, by means of conditionality, IADB can influence the format and content of public policies, specially the Procentro one. It was noted that the conditionality is a premise that condition the Contract signature, being it limited to an instrument of guarantee for the loan repayment, what implies in the logic of ‘cost-benefit’ (the Bank thus considers only the measurable aspects). For that, the Bank demands a series of managerial procedures that define the modus operandi of financing, as well as determines management forms known as ‘best practices’ as standard. In regards to the analysis of different political/partisan management, it was possible to notice the option taken by the IADB of not valuing popular participation, as well as ignoring the demands posed by social movements representing the poor part of the population. When analyzing the documents, it was observed that IADB has a particular approach in relation to public policies using as base international experiences considered by it as successful. Finally, the documents signed with the government are of difficult access, an indicative of low transparency.